Aladdin and the king of thieves [videorecording (DVD)] - Waters, Mark S., 1964-; Johnson, Carl, 1965- (Disney DVD., 2005)
People near and far are heading for Agrabah as the royal wedding of the century is about to take place. But before Aladdin and Jasmine can say "I do," the legendary Forty Thieves spoil everything in a desperate search for the powerful Hand of Midas -- the ultimate treasure that turns all it touches into gold.